The Alkaloids of Ophiorrhiza communis and O. tomentosa - Hamzah, Ahmad Sazali; Arbain, Dayar; Mahyudin,; V. Sargent, Malviyn; Lajis, Md Nordin (Universiti Putra Malaysia Press, 1994)
Two alkaloids, harman and strictosidinic acid, were isolated from the leaves and bark of Dphiorrhiza communis Linn. Strictosidinic acid was also isolated from Dphiorrhiza tomentosa Jack. These structural assignments were based on their physical and spectroscopic data.